(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Rashevska N. V., Tkachuk V. V. Mobile learning technologies. The article contains several definitions of mobile learning, shows its advantages and disadvantages, discussed several areas of the implementation of mobile learning, in particular, to construct a model of blended learning.